OCCUPYING POLICY SPACES: EXPLORING THE ASCENDENCY POTENTIAL OF RELIGION AND THEOLOGY IN GOVERNANCE AND PUBLIC POLICY DISCOURSE IN SOUTH AFRICA - Nzewi, O. I. (Scriptura, 2013)
The aim of this article is to seek an understanding of why there seems to be policy reluctance in acknowledging the potential of practice and academic theology in governance and policy development in South Africa. This study examines these issues from an interdisciplinary perspective. The provocative thesis in this paper is that religion and theology belong in the public sphere. The approach in this paper is to use an informed knowledge of public policy and issues, to engage the implications of what is at stake, and subject this to sharp analytical evaluation and theological critique. Drawing from institutionalism and policy studies, the article examines the change potential of religion and theology within a constitutional democracy, the point of departure being the acknowledgement of a critical distinction between public policy discourse and public discourse. The article takes a premise that although it may have been best left alone by many social and political scientists, religion remains - despite the popularity of the secularism theorists - resilient as part of people’s value systems and social identity.